Magpie murders [videorecording (DVD)] - Horowitz, Anthony, 1955-; Manville, Lesley; McMullan, Tim; Hill, Conleth, 1964-; Maloney, Michael, 1957-; Logothetis, Alexandros; Rushbrook, Claire; Mays, Daniel; Beard, Matthew, 1989-; Horowitz, Anthony, 1955- (PBS Distribution, 2022)
A beguiling murder mystery with a solution that will both astonish and shock viewers, the plot revolves around the character Susan Ryeland, an editor who is given an unfinished manuscript of author Alan Conway's latest novel, but has little idea it will change her life.